Perancangan Tampilan Antarmuka pada Aplikasi Selfqure dengan Menerapkan Metode Design Thinking - Samanjaya, I Gede Arisudana; Dwidasmara, Ida Bagus Gede (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 2 No 1 (2023): JNATIA Vol. 2, No. 1, November 2023DO - 10.24843/JNATIA.2023.v02.i01.p19, 2023)
Mental health disorders in adolescents are influenced by factors such as social pressure, identity exploration, violence, harsh parenting, and socio-economic problems. The lack of understanding and stigma surrounding mental health issues often leads adolescents to avoid discussing their problems, resulting in potential risks to their well-being. To address this, the development of mobile applications like "Selfqure" focuses on providing information and treatment for mental health problems in adolescents. By utilizing design thinking principles, the application aims to enhance user experience and interface, increase understanding, reduce stigma, and improve access to support. Usability testing of the app yielded a score of 82, indicating satisfactory acceptance and usability among the target age group. This highlights the importance of innovative solutions to tackle mental health challenges and promote well-being in adolescents.